A probable new syndrome with the storage disease phenotype caused by the VPS33A gene mutation. Issue 1 (January 2017) - Dursun, Ali; Yalnizoglu, Dilek; Gerdan, Omer F.; Yucel-Yilmaz, Didem; Sagiroglu, Mahmut S.; Yuksel, Bayram; Gucer, Safak; Sivri, Serap; Ozgul, Riza K.
Abstract : We present a novel multisystem disease in two siblings with clinical features resembling a lysosomal storage disease. These included coarse face, dysostosis multiplex, respiratory difficulty, proteinuria with glomerular foamy cells, neurological involvement with developmental delays, pyramidal signs, and severe chronic anemia. Detailed enzymatic analysis for lysosomal diseases and whole-exome sequencing studies excluded known lysosomal storage diseases in the proband. Subsequently, genome-wide genotyping and exome sequencing analysis of the family indicated two large homozygous regions on chromosomes 5 and 12, and strongly suggested that a homozygous p. R498W missense mutation in the VPS33A gene might be responsible for this novel disease. Segregation analysis in family members and mutation prediction tools' results also supported the damaging effect of the missense mutation on the function of the Vps33a protein, which plays a role in the vesicular transport system. Electron microscopic studies of the cornea of the proband showed findings supportive of dysfunction in vesicular transport. The clinical phenotype and genetic studies support the suggestion that the siblings most probably have a novel disease very likely caused by a VPS33A gene defect.